"Путешествие из Петербурга в Москву" А.Н. Радищева: кн. для учащихся / Ю.К. Бегунов - Бегунов Юрий Константинович (Просвещение, 1983)
Экземпляры: АБ (1984) / Инвентарный номер: 8132 / Авт.знак: Б 37 / ГРНТИ: 17.09 / ББК: 83.3Р1